Variation in susceptibility of laboratory and field strains of three stored-grain insect species to β-cyfluthrin and chlorpyrifos-methyl plus deltamethrin applied to concrete surfaces - Sehgal, Blossom; Subramanyam, Bhadriraju; Arthur, Frank H.; Gill, Bikram S. (My University, 2013)
The efficacy of commercial formulations of β-cyfluthrin and chlorpyrifosmethyl plus deltamethrin applied to clean, concrete surfaces similar to that of empty bins against field strains of stored-grain insects is unknown. We exposed adults of 16 strains of the red flour beetle, Tribolium castaneum (Herbst); 8 strains of the sawtoothed grain beetle, Oryzaephilus surinamensis (L.); and 2 strains of the lesser grain borer, Rhyzopertha dominica (F.), collected mainly from farm-stored grain in Kansas, USA, to β-cyfluthrin and chlorpyrifos-methyl plus deltamethrin applied to concrete surfaces and determined knockdown and mortality. RESULTS: Knockdown and mortality differences among species and strains to the insecticides tested were significant. Mortality of all species was less than that of knockdown, suggesting recovery when placed on food after insecticide exposure. β-cyfluthrin was effective against R. dominica but ineffective against T. castaneum and O. surinamensis field strains. Chlorpyrifosmethyl plus deltamethrin was only partially effective against field strains of the three species. CONCLUSION: Reduced susceptibility in field strains may be due to inherent formulation deficiency and low levels of tolerance or resistance to β-cyfluthrin. No single insecticide provided adequate control of the three species tested.
Citation: Sehgal, B., . . . & Gill, B. (2013). Variation in susceptibility of laboratory and field strains of three stored‐grain insect species to β‐cyfluthrin and chlorpyrifos‐methyl plus deltamethrin applied to concrete surfaces. Pest Management Science, 70(4), 576-587. https://doi.org/10.1002/ps.3580
Keywords: Insecticides; Empty-bin treatments; Stored-grain insects; Field strains; Efficacy assessment